2009
DOI: 10.1007/s00424-009-0676-9
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor β activation promotes myonuclear accretion in skeletal muscle of adult and aged mice

Abstract: We reported recently that peroxisome proliferatoractivated receptor β (PPARβ) activation promotes a calcineurin-dependent exercise-like remodelling characterised by increased numbers of oxidative fibres and capillaries. As physical exercise also induces myonuclear accretion, we investigated whether PPARβ activation alters myonuclear density. Transgenic muscle-specific PPARβ over-expression induced 14% increase of myonuclear density. Pharmacological PPARβ activation promoted rapid and massive myonuclear accreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…These data, together with previously published reports (19,23,51), strongly support a role for PPAR␤/␦ in positively regulating postnatal skeletal muscle growth. However, in contrast to the results presented here, previously published data from Dressel et al (44) describe that GW501516-mediated activation of PPAR␤/␦ does not affect myogenic differentiation of C2C12 myoblasts.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These data, together with previously published reports (19,23,51), strongly support a role for PPAR␤/␦ in positively regulating postnatal skeletal muscle growth. However, in contrast to the results presented here, previously published data from Dressel et al (44) describe that GW501516-mediated activation of PPAR␤/␦ does not affect myogenic differentiation of C2C12 myoblasts.…”
Section: Discussionsupporting
confidence: 86%
“…Pharmacological activation of the muscle-specific PPAR␤/␦ isoform promotes muscle development, myonuclear accretion, and satellite cell proliferation and restores sarcolemmal integrity in dystrophic mice models (17,19,23,50,51), strongly supporting a role for PPAR␤/␦ in regulating postnatal muscle growth and development. However, no study has yet clearly revealed the molecular mechanism(s) through which PPAR␤/␦ regulates skeletal muscle growth.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In agreement with this, overexpression of a constitutively active PPAR␤/␦ in mouse skeletal muscle was found to induce differentiation of mitochondria-rich, oxidative type I muscle fibers (42). In addition, muscle-specific overexpression of PPAR␤/␦ has been shown to promote myonuclear density (13). PPAR␤/␦ also plays an important role in the adaptation of skeletal muscle to environmental changes, such as long-term fasting, by increasing the number of oxidative fibers (10).…”
mentioning
confidence: 48%
“…Increased myonuclear density has been found in transgenic muscle-specific over-expressing animals, as well as in wild-type mice treated for only 2 days with a PPARb agonist. As mouse aging is associated with reduced PPARb expression, and with decreased numbers of oxidative myofibres and myonuclei, which could be partially reversed by pharmacological PPARb activation, a potential use of PPARb agonists for the treatment of age-related muscle atrophy has been suggested [43].…”
Section: Discussionmentioning
confidence: 99%